Software Project Management as Team Building Intervention - Mohammad Khalid Shaikh,; Akhtar Raza ,; Kamran Ahsan, (Journal of Basic & Applied Sciences, 2016)
The courses of software project management (SPM) and Software engineering (SE) are regularly taught at undergraduate degree program in computer science. Students of these programs also have to undertake projects as part of various courses during their degree program. The purpose of this research is to assess whether the software engineering or the software project management course had enhanced the cohesion among team members while undertaking a six month or a year-long project. The teaching of these two courses is considered as a team building intervention in this research. A total of 167 students returned a modified version of Group Environment Questionnaire distributed to 200 students. Off these, 81 were those who had taken the SE course and subsequently did a project before they had taken SPM course. The rest of the students (85) consisted of those who had taken SPM and had undertaken final project. The results of this paper indicates that the SPM as compared to SE as a team building intervention had a better effect on team cohesion. The paper has successfully identified a single course that can enhance the performance of students as a team in contrast to proposing all the courses taught at the undergraduate computer science degree program as intervention for better team building and team work as proposed by Hogan & Thomas, 2005.